Hierarchical Structures: Programmable Building Blocks via Internal Stress Engineering for 3D Collective Assembly (Adv. Mater. Technol. 12/2020). Issue 12 (9th December 2020) - Cho, Woongbi; Hahm, Dong Yoon; Yim, Jae Ha; Lee, Jun Hee; Lee, Yun Ju; Kim, Dong‐Gyun; Kim, Yong Seok; Wie, Jeong Jae
Abstract : In article number 2000758, Jeong Jae Wie and co‐workers present a nature‐inspired collective assembly of precisely designed 3D building blocks for scaled‐up hierarchical 3D architectures. The precise dimension control of 3D building blocks is successfully progressed by controlling the spatio‐temporal effect composed of fractal elements throughout the stages of fabrication. The concept of collective assembly extends the morphological diversity of the 3D structures and presents a construction of creatively assembled structures.